2010
DOI: 10.1074/jbc.m110.143321
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Residues of the 39-Loop in Determining the Substrate and Inhibitor Specificity of Factor IXa

Abstract: The activation of antithrombin (AT) by heparin facilitates the exosite-dependent interaction of the serpin with factors IXa (FIXa) and Xa (FXa), thereby improving the rate of reactions by 300-to 500-fold. Relative to FXa, AT inhibits FIXa with ϳ40-fold slower rate constant. Structural data suggest that differences in the residues of the 39-loop (residues 31-41) may partly be responsible for the differential reactivity of the two proteases with AT. This loop is highly acidic in FXa, containing three Glu residue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…However, although the FIXa mutant exhibited a normal affinity for FVIIIa, its catalytic activity (k cat ) toward the natural substrate FX in the presence of FVIIIa was decreased ϳ4-fold, suggesting that residues of the 39-loop contribute to the recognition specificity of the substrate in the intrinsic tenase complex (10). Further studies revealed that the reactivity of the FIXa mutant with AT has been improved ϳ5-fold specifically in the absence of pentasaccharide, suggesting that the 39-loop of FIXa contributes to the slower reactivity of the protease with the serpin in the absence of a heparin cofactor (10). In light of the latter observation that the 39-loop of FXa improves the recognition specificity of the FIXa chimera with the circulating native conformer of AT, we wondered whether the 39-loop of FIXa plays any role in rendering FIXa resistant to inhibition by other plasma inhibitors, which readily inhibit FXa in circulation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, although the FIXa mutant exhibited a normal affinity for FVIIIa, its catalytic activity (k cat ) toward the natural substrate FX in the presence of FVIIIa was decreased ϳ4-fold, suggesting that residues of the 39-loop contribute to the recognition specificity of the substrate in the intrinsic tenase complex (10). Further studies revealed that the reactivity of the FIXa mutant with AT has been improved ϳ5-fold specifically in the absence of pentasaccharide, suggesting that the 39-loop of FIXa contributes to the slower reactivity of the protease with the serpin in the absence of a heparin cofactor (10). In light of the latter observation that the 39-loop of FXa improves the recognition specificity of the FIXa chimera with the circulating native conformer of AT, we wondered whether the 39-loop of FIXa plays any role in rendering FIXa resistant to inhibition by other plasma inhibitors, which readily inhibit FXa in circulation.…”
Section: Resultsmentioning
confidence: 99%
“…The expression and purification of the FIX mutant in which the residues of the 39-loop from residues Val 31 to Phe 41 ( 31 Val-Val-Leu-Asn-GlyLys-Val-Asp-Ala-Phe 41 ) in the chymotrypsin numbering (12) were replaced with the same 39-loop residues of FXa ( ) using the same expression/purification vector system have been described (10). The activation of FIX derivatives by the FXactivating enzyme from Russell's viper venom and determination of their active site concentration by an amidolytic activity assay and active site titrations using known concentrations of AT in the presence of heparin have been described (13).…”
Section: Construction Mutagenesis and Expression Of Recombinantmentioning
confidence: 99%
See 3 more Smart Citations